Historical memory in language and socio-historical discourse - Belikova, Natalia Yu.; Voskoboynikov, Sergey G.; Schukina, Tatyana V.; Topchiy, Inna V.; Vakula, Ivan M.; Kharchenko, Liubov N. (Universidade Estadual Paulista, 2021)
Generally, collective memory, or historical memory, applies to the shifting way by which collections of individuals build and then recognize with particular narratives concerning historical times or occasions, often based on today's conditions. The article's primary purpose is to consider the problem of historical memory in the framework of langue and socio-historical discourse. The article attempts to demonstrate the close interweaving of historical memory, linguistics, and socio-historical discourse with social memory. To gratify the aim of the idea, the interdisciplinary, sociocultural, and historical-social approaches; methods of qualitative analysis (content analysis, comparative analysis) are taken into consideration. Therefore, based on the results acquired m, it can be concluded that historical experience is the trigger mechanism that starts the operation of social memory. Plus, the properties of historical memory are indicated, such as virtuality, objectivity, mobility. Exploring historical memory, the authors relied on a multilevel approach.